2013
DOI: 10.1292/jvms.12-0464
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Triceps Tendon Avulsion in a Dog: Magnetic Resonance Imaging and Surgical Management Evaluation

Abstract: We report here the clinical presentation, magnetic resonance imaging (MRI) findings and successful surgical management associated with triceps tendon avulsion in a dog. A definitive diagnosis of triceps tendon avulsion was made based on MRI with evidence of displacement of the triceps tendon. Surgical correction of triceps tendon avulsion was performed with two horizontal mattress sutures using polyester and two tunnels drilled in the olecranon to reattach the tendon to the proximal olecranon. At 9 months, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 7 publications
(19 reference statements)
1
33
0
Order By: Relevance
“…This study reported the characteristics of triceps brachii tendon injury, which, to the author’s knowledge, has only been described in a few cases among cats and dogs [ 2 , 3 , 5 , 13 , 20 ]. This is the first report to describe multiple cases of this injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study reported the characteristics of triceps brachii tendon injury, which, to the author’s knowledge, has only been described in a few cases among cats and dogs [ 2 , 3 , 5 , 13 , 20 ]. This is the first report to describe multiple cases of this injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reports discussing the tendon fragility of Pomeranians in comparison with other breeds, variations in the predisposition of different breeds should be considered. A previous study also reported a case of Pomeranian with triceps tendon injury [ 20 ]; however, there was no histopathological examination of the triceps brachii. The potential weakness of the triceps brachii tendon in Pomeranians needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Tendon injuries in dogs include rupture, avulsion, laceration, contusion, strain and luxation. [2][3][4] Although some articles have reported rupture, avulsion, and laceration of the triceps brachii tendon, [5][6][7] luxation of this tendon has not been reported. Elbow luxation and subluxation can occur by traumatic, congenital, and developmental causes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 11 cases (2 cats, 9 dogs) of triceps tendon rupture and/or avulsion have been reported in the veterinary literature. [3][4][5][6][7][8][9][10] A further case report was in fact a cat with an olecranon avulsion fracture. 4 Previous historical indings have been acute trauma, corticosteroid treatment or chronic lameness.…”
Section: Introductionmentioning
confidence: 99%